Masterplan Kawasan Wisata dan Edukasi Muhammadiyah Ponorogo berbasis Potensi Lokal untuk Pengembangan Perekonomian - Hartono, Sri; Purnomo, Rochmat Aldy; Rachmadia, Rizki; Futaqi, Faruq Ahmad; Sumarsono, Hadi; Wijayanto, Heri; Sritrisniawati, Shella Elly (Jurnal SOLMA, 2024)
The Muhammadiyah Ponorogo Regional Leadership received 1.2 hectares of waqf land located in Plalangan Village, Jenangan, Ponorogo which can be used as a tourism business charity. Limited human resources are an obstacle in the arrangement and use of waqf land and more comprehensive spatial planning is needed involving all stakeholders. This program aims to increase the potential of waqf land to become a Muhammadiyah tourist village based on local potential for economic development. The partners of this program are elements of institutions under the authority of the Muhammadiyah Ponorogo Regional Leadership with 50 participants consisting of economic and business as well as tourism councils and elements of the community around Plalangan, Jenangan, Ponorogo. The method used was to present and create a master plan for the Muhammadiyah Ponorogo Tourism Village. The results of the program show that with the activities carried out, there has been a change from not having the potential of waqf land to become a Muhammadiyah tourist village based on local potential to understanding and having the potential of waqf land to becoming a Muhammadiyah tourist village based on local potential. It can be concluded that there has been an increase in skills among partners regarding the potential of waqf land to become a Muhammadiyah tourist village based on local potential.